DEVELOPMENT OF PROFESSIONAL COMPETENCE OF COLLEGE TEACHERS: TECHNOLOGIES AND APPROACHES (Innovative professional education, 2025)
The professional competence of a teacher includes mastery of modern teaching methods, the ability to innovate, flexibility in the use of technologies and adaptation to the needs of students. In this context, pedagogical technologies play a significant role, contributing to the systematic development of the professional and personal qualities of a teacher
Keywords: professional competence, college teacher, learning technologies, continuing education